Immanent Realism An Introduction to Brentano - Albertazzi, Liliana (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science,, 2006)
In many respects, Brentano conducted pioneering analyses of problems that are currently in the focus of cognitive science and artificial intelligence: from the problem of reference to that of representation, from the problem of categorial classification to ontology and the cognitive analysis of natural language. Brentano, in fact, dealt with and wrote on questions concerning the auditory stream (temporal apprehension), visual perception (continua, point of view, three-dimensional construction of phenomenal objects), intentionality, imagery, and conceptual space, considering these pertaining to a metaphysical enquiry. Moreover, Brentano displayed clear awareness of the complexity of problems and of the interrelations among different areas of inquiry. From this point of view, his theory, however complex, offers elements for the treatment of problems currently under investigation. Brentano's work is an antidote against physicalism and logicism, which dominated the 20th century epistemology, and as such appears to be a good philosophy candidate for cognitive science. "A set of knotty questions are implied in the very title of Brentano's work "Psychology from an empirical standpoint". To solve them, Albertazzi guides us systematically through Brentano's life and works, investigating into the inherent complexity of both his view of mental life and the related methodology. In so doing, she discloses a number of threads into the open texture of modern philosophy of mind." Lia Formigari, Ordinary professor of Philosophy of Language, La Sapienza, Rome, Italy.